DESAIN PEMBELAJARAN KELAS ANTI-KLITHIH - Ermawati Ermawati; Joko Santoso (CARAKA, 2018)
This paper is a journal review that became the main reference research of Penelitian Dosen Pemula, Ristek Dikti 2017 entitled "Desain Pembelajaran Kelas Anti-Klithih Berbasis Intrapersonal Intelligence dengan Media Audio-Visual Pada SMA/SMK/Sederajat Se-Kabupaten Bantul". The selected journals are the last three (3) years of recent journals on violence, learning, and school curriculum. Journals are international journals obtained through ebscohost and google scholar with the keywords: bullying in schools and school violence. As a result, the six journals each encourage constructive learning design efforts that take into account the role of social, democratic leadership, expertise, multiculturalism, and regulation